Interlaminar crack propagation in MWCNT/fiber reinforced hybrid composites (eXPRESS Polymer Letters, 2009)
In this work carbon fiber/epoxy composites and MWCNT (multiwalled carbon nanotube)/carbon fiber/epoxy hybrid composites with 0.1, 0.3, 0.5 and 1 weight% nanotube filling of the matrix have been prepared and compared in terms of interlaminar properties. For the dispersion of the carbon nanotubes in the epoxy resin three roll milling has been utilized. The mechanical characterization has been carried out using standard DCB (double cantilever beam) tests assisted by acoustic emission. The test results have been evaluated by the conventional method provided by the standard and a novel method implementing acoustic emission signal localization for crack propagation tracing. According to the tests carbon nanotube filling of the matrix of the composites has a beneficial effect on their interlaminar properties: the interlaminar fracture toughness values of the composites have increased by a maximum of 13 and 33% at a 0.3 weight% carbon nanotube content of the matrix according to the conventional and AE based evaluation method respectively.